Projeto conceitual de uma máquina de corte: uma proposta de melhoria do processo de beneficiamento do palmito picado - MERCÊS, Edner Silva das (2022)
The objective of this study is to propose the conceptual design of a machine for crushing palm to meet a demand for process improvement in factories in the city of Abaetetuba, because the cutting operation manual is considered unproductive, offer little standardization in size of cut of palm chopped and risks of accidents with the handling of knives. For the development of the conceptual design was used model of Unified Reference, along with this model of development of product were applied the tools known as Project Model Canvas, House of Quality, morphological matrix, functional modeling and 3D digital modeling with the Skecthup® software, obtaining success in the conceptual modeling of the product with the digital mock-up of the machine to chop-palm.